2021
DOI: 10.1016/j.techsoc.2020.101465
|View full text |Cite
|
Sign up to set email alerts
|

Telehealth and COVID-19: Using technology to accelerate the curve on access and quality healthcare for citizens in India

Abstract: The current COVID-19 pandemic has reinstated the importance of telehealth as a business model for accelerating the accessibility of healthcare and improving the quality of healthcare for citizens of a country. Telehealth service has a tremendous potential in a developing country like India where the healthcare facilities in India are heavily concentrated in urban cities while their majority (67%) of the population resides in rural areas. At the same time, a high teledensity of almost 90% supports telehealth ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 32 publications
0
34
0
1
Order By: Relevance
“…However, studies in China 37 , 38 and Russia 39 , 40 have identified increasing adoption of telemedicine applications among their citizens; however, there are a few issues, including ineffective legal regulations and a lack of transparency and privacy, that are affecting the adoption of telemedicine in these countries. Similarly, India 42 , 43 and Brazil 41 are also expanding the adoption of telemedicine solutions, but remoteness and a lack of access to technology are affecting the adoption of telemedicine while an ever-increasing prevalence of chronic, lifestyle and long-term illnesses is increasing the demand for telemedicine in these countries. Comparing the results from Saudi Arabia, it is clear that security concerns such as privacy are one of the major obstacles identified in the implementation of telemedicine, similar to India, while positive attitudes towards telemedicine were identified among participants, similar to the BRICS nations.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies in China 37 , 38 and Russia 39 , 40 have identified increasing adoption of telemedicine applications among their citizens; however, there are a few issues, including ineffective legal regulations and a lack of transparency and privacy, that are affecting the adoption of telemedicine in these countries. Similarly, India 42 , 43 and Brazil 41 are also expanding the adoption of telemedicine solutions, but remoteness and a lack of access to technology are affecting the adoption of telemedicine while an ever-increasing prevalence of chronic, lifestyle and long-term illnesses is increasing the demand for telemedicine in these countries. Comparing the results from Saudi Arabia, it is clear that security concerns such as privacy are one of the major obstacles identified in the implementation of telemedicine, similar to India, while positive attitudes towards telemedicine were identified among participants, similar to the BRICS nations.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, ICT usage is beneficial for increasing the scope and availability of medical services; our findings indicate that it might be practical in rural areas. Many medical facilities in urban areas have started using ICT to communicate with distant patients [35,36]. Metropolitan areas and hospitals might be best suited to use ICT to effectively prevent infections [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…These people are aware of health issues [ 17 ] and are interdependent [ 37 ]. As more developing countries are adopting various telehealth platforms to administer healthcare [ 38 ], Bangladeshis are following suit. As a result, a significant portion of the population has adopted smartwatches to monitor their health.…”
Section: Introductionmentioning
confidence: 99%